1999
DOI: 10.1073/pnas.96.21.11782
|View full text |Cite
|
Sign up to set email alerts
|

Nonstatistical binding of a protein to clustered carbohydrates

Abstract: Carbohydrate-derivatized self-assembled monolayers (SAMs) are used as a model system to address issues involving cell-surface carbohydrate-protein interactions. Here we examine the influence of carbohydrate surface density on protein-binding avidity. We show that the binding selectivity of Bauhinia purpurea lectin switches from one carbohydrate ligand to another as the surface density of the carbohydrate ligands increases from values of sugar Ϸ 0.1-1.0. Polyvalent binding is possible at all surface densities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
166
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(175 citation statements)
references
References 28 publications
6
166
1
2
Order By: Relevance
“…Also, multivalency can be mimicked by local clusters as in branched glycans (35)(36)(37)(38)(39)(40)(41)(42). Parallel experiments on monolayers to characterize cis interactions plus consideration of presence of cholesterol and sphingolipids for microdomain generation would further broaden the scope, together with consideration of secondary effects (43). In this way, structurally programmed amphiphilic Janus glycodendrimers or mixtures of respective preparations have the enormous potential to shed light on fundamental aspects of structure-activity relationships within the process of how specific carbohydratelectin interactions are realized and enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Also, multivalency can be mimicked by local clusters as in branched glycans (35)(36)(37)(38)(39)(40)(41)(42). Parallel experiments on monolayers to characterize cis interactions plus consideration of presence of cholesterol and sphingolipids for microdomain generation would further broaden the scope, together with consideration of secondary effects (43). In this way, structurally programmed amphiphilic Janus glycodendrimers or mixtures of respective preparations have the enormous potential to shed light on fundamental aspects of structure-activity relationships within the process of how specific carbohydratelectin interactions are realized and enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Solid Supports-Receptor binding, activation, and endocytosis have been studied using functionalized beads and surfaces. [127][128][129][130] The beads employed in these investigations vary in composition; they can be derived polystyrene, latex, polysaccharides, or other insoluble materials. The typical reactions used to conjugate binding epitopes to beads are straightforward and general, though rarely are these processes chemoselective or regioselective.…”
Section: 3b Proteinmentioning
confidence: 99%
“…[9,129,[216][217][218] In this way, a study addressing the mechanism by which T cell responses are enhanced by the co-receptor CD28 was undertaken. [87] Ligand binding to the TCR is necessary and sufficient for activation of T cells; however, co-stimulation of CD28 yields a more potent response.…”
Section: 1b G-protein Coupled Receptors (Gpcrs)-gpcrsmentioning
confidence: 99%
“…Investigators have previously observed greater specificity on the part of lectins for polyvalent ligands as compared with their monovalent counterparts (15)(16)(17)(18)(19)(20)(21)(22). The specificity for multivalent ligands has been attributed to a requirement for unique spacing patterns (15)(16)(17)(18), secondary protein-protein and protein-carbohydrate interactions (19,20), and amplification in the polyvalent state of small differences in the affinities between monovalent forms (21). One prediction of a model in which small differences in affinity of monovalent ligands are amplified in the polyvalent state is that the affinities obtained for Mu11 binding to immobilized S4GGnM-BSA and S3GGnM-BSA would differ but that the B max obtained at saturation would be the same.…”
Section: Specificity Of the Cys-rich Domain For Monovalent Ligands-wementioning
confidence: 99%